Family caregivers' accounts of caring for a family member with motor neurone disease in Norway: a qualitative study. Issue 1 (December 2016) - Lerum, Sverre; Solbrække, Kari; Frich, Jan
Abstract Background Motor neurone disease (MND) is a progressive neurological disease causing muscle wasting, gradual paralysis, respiratory failure. MND care is demanding, complex and involves a variety of care tasks. Family members may experience significant and enduring strain. We conducted a qualitative study to understand more about family caregivers' work and sense of responsibility, exploring family caregivers' accounts of caring for a family member with MND. Methods We recruited and interviewed a total of 25 participants from Norway, including 17 current and eight bereaved family caregivers. Drawing on theories of care by Corbin and Strauss, we analysed the data by a theoretical reading of the material to identify different types of care work. Results We found that caregivers were engaged in five lines of care work that could be parallel or closely interconnected: i) immediate care work; ii) seeking information and clarity about the disease; iii) managing competing obligations; iv) maintaining normality; and v) managing external resources and assistance. Caregivers' priorities were shaped by their interactions with the person with MND, available assistive devices, the development of the illness, and utilisation of paid care. Care work had a symbolic and moral meaning for caregivers, and was associated with self-worth and respect from others. Caregivers tried to balance their own expectations and others' expectations without being overwhelmed by care work. Conclusions A changing and potentially chaotic situation for family caregivers may compromise their capacity to utilise supportive services. Using the lines of work as a framework to assess caregivers' preferences and priorities, health professionals may tailor assistance and support to family members caring for persons with MND.